ANALYSIS OF THE EFFECT OF LEADERSHIP COMMITMENT ON THE RELATIONSHIP BETWEEN FACTORS AFFECTING THE QUALITY OF FINANCIAL STATEMENTS IN THE DIRECTORATE OF HIGHER EDUCATION IN THE MINISTRY OF RESEARCH, TECHNOLOGY AND HIGHER EDUCATION - Gultom, Shohifah (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study was to analyse the commitment of the leadership as a mediator of the relationship between the quality of human resources, supporting infrastructure, compliance with regulations, the accrual-based agency accounting systems applications to the quality of the financial statements of the Ministry of Technology and Higher Education. In this study structural equation modelling is used to analyse the relationship between the quality of human resources, supporting infrastructure, compliance with regulations, the accrual-based agency accounting systems application to the quality of financial statements. Data was collected by distributing questionnaires to SAI officers in the work unit of the directorate of higher education at the research, technology, and higher education ministries at the meeting for preparation at the first semester of 2017 financial statements and the financial report preparation meeting in 2017. SEM data was used with the help of software AMOS. The results showed that the ability of human resources, supporting facilities and infrastructure, compliance with regulations, and the application of an accrual-based agency accounting system (SAI-BA) had an effect both simultaneously and partially on the quality of financial reports in the ministries of research, technology, and higher education.  Leadership commitment has not been able to mediate the relationship between human resource capabilities, supporting facilities and infrastructure, compliance with regulations, and the application of accrual-based agency accounting systems (SAIBA) with the quality of financial reports in the ministries of research, technology, and higher education.